How does ethnomathematics work within an online platform? - Peni, Nur Robiah Nofikusumawati (Journal of Education for Sustainability and Diversity, 2022)
Recently, ethnomathematics has emerged as one of the promising approaches for assisting teachers in promoting culture in the lives of their students. However, ethnomathematics left a strong impression that it was primarily concerned with cultural issues and was difficult to integrate with technology. Because the image of traditional ethnomathematics has become in contrast with the new era nowadays, where the online platform is used during the teaching-learning process during this pandemic situation, the usage of ethnomathematics has decreased. The essence of ethnomathematics, which requires face-to-face learning, posed a new challenge to applying this approach in the digital age. This study aims to investigate the characteristics of ethnomathematics and how they interact with online platforms. This literature review gathers information from previous studies in which several online platforms work with students with or without culture as a context in the teaching-learning process. The findings show that the characteristics of ethnomathematics and those online platforms are intertwined and that this could be a new approach to promoting culture within the mathematics learning process.